Taekwondo training on athlete`s physical injury mechanism in plateau ecological environment - Fang, W.; Liu, S. (Caribbean Journal of Science, 2019)
The level of energy metabolism of Taekwondo athletes directly affects athletes` performance. In order to better improve the physical function and athletic performance of Taekwondo athletes, it is necessary to find new training methods. Through experiments and other methods, 7 athletes from the plateau were tested in the 33-day plateau ecological environment during the training period to explore the effects of training on physical function in the plateau ecological environment, so that they can play the plateau ecological environment within the scheduled time. The training effect provides a reference. The results showed that the blood index showed a trend of decreasing first and then rising, and returned to the pre-training level until the end of training; VO2 max showed no significant change; CK and BUN changed within the normal range; testosterone value and T/C ratio increased significantly. Conclusion: The athletes of the plateau have improved and improved their blood level indicators and hormone levels after training in the plateau ecological environment, and their exercise capacity has been improved.